2003
DOI: 10.1002/eji.200323377
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of allergen‐specific IgE production and suppression of an established Th2‐type response by immunization with DNA encoding hypoallergenic allergen derivatives of Bet v 1, the major birch‐pollen allergen

Abstract: In atopic patients, programming towards a preferential Th2 immunity leads to IgE antibody production and cellular Th2 immunity against otherwise harmless antigens. We report the development of prophylactic and therapeutic DNA vaccines for the major birch-pollen allergen, Bet v 1. We constructed three DNA vaccines, coding for the complete cDNA, coding for two hypoallergenic fragments or coding for a hypoallergenic Bet v 1 mutant. The protective effect was studied in mice pretreated by intradermal DNA injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 25 publications
(36 reference statements)
2
55
0
2
Order By: Relevance
“…30), where the capability of Cyp c 1-specific IgE Abs to induce degranulation of RBL cells after contact with Cyp c 1 was analyzed.…”
Section: Immunization Of Mice and Determination Of Ag-specific Igg1 Amentioning
confidence: 99%
“…30), where the capability of Cyp c 1-specific IgE Abs to induce degranulation of RBL cells after contact with Cyp c 1 was analyzed.…”
Section: Immunization Of Mice and Determination Of Ag-specific Igg1 Amentioning
confidence: 99%
“…Among them, Bet v 1, the major allergen of birch pollen, belongs to the most extensively studied molecules [9,15,16,17,18]. These studies have demonstrated that DNA-based immunization with a construct encoding Bet v 1 mounted Th1-biased specific immune responses and protected against allergic sensitization.…”
Section: Th1-biased Immunity – the Key To Dna-based Allergy Vaccinationmentioning
confidence: 93%
“…Neither blocking antibodies nor T regulatory cells or other tolerance-related responses play a major role in effective protective and therapeutic antiallergic DNA-based reactions [9]. …”
Section: Th1-biased Immunity – the Key To Dna-based Allergy Vaccinationmentioning
confidence: 99%
“…Allergens that are chemically coupled to virus-like particles [65,66] Genetic vaccines DNA vaccines -Vaccination with allergen-encoding DNA [88][89][90][91][92][93] RNA vaccines -Vaccination with allergen-encoding RNA [94] B. Alternative routes Sublingual -Sublingual administration of allergen-containing drops or tablets [17,24,[74][75][76][77][78][79] Oral -Oral administration of allergens (i.e.…”
Section: Coupled Allergensmentioning
confidence: 99%
“…The advantage of using allergen-encoding DNA instead of allergen for vaccination is, however, outweighed by the concern that genetic immunization may induce an uncontrolled production of allergens in treated subjects and thus may cause side effects [92]. To overcome this problem, genetic vaccination with DNA coding for hypoallergens has been considered as an alternative approach [93]. Furthermore, RNA immunization that gives rise to only transient allergen production has been considered as a possible alternative [94].…”
Section: Genetic Immunizationmentioning
confidence: 99%